The doctrine of deification in the Greek patristic tradition - Russell, Norman, 1945- (Oxford early Christian studies, 2006)
Deification was not only a pagan concept but a metaphor for a deeply Christian view of the purpose of human life. The author brings together research on the Church Fathers from the second to the seventh centuries, offering an analysis of their spiritual teaching and setting it within the context of the times.